Pengaruh Budaya Kerja dan Disiplin Kerja terhadap Produktivitas Kinerja Karyawan di PT. CKL Indonesia Raya - Missella Anugrah Widia; Purwatiningsih Purwatiningsih (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
PT. CKL Indonesia Raya is a national logistics company established in 2015 in Jakarta, providing services in land, sea, air, and export-import logistics. Recognized for its professionalism and discipline, the company was awarded “Airfreight Forwarder of the Year 2024” by Supply Chain Indonesia. Employee productivity plays a crucial role in determining organizational success, and factors such as work culture and discipline are key in shaping a productive and competitive work environment. This study aimed to analyze the influence of work culture and discipline on employee productivity at PT. CKL Indonesia Raya. The research employed a quantitative method with a survey approach, using questionnaires distributed to 86 employees as respondents. Validity and reliability tests confirmed the appropriateness of the instrument. Data analysis was conducted using t-tests and F-tests. The results showed that both work culture and discipline had significant partial effects on employee productivity (t-count = 4.550 and 5.116 > t-table = 1.663; sig. = 0.001 < 0.05). Furthermore, the simultaneous test indicated a significant combined effect (F-count = 125.092 > F-table = 3.10; sig. = 0.001 < 0.05). These findings demonstrate that strong work culture and high discipline significantly contribute to enhancing employee productivity. Therefore, companies are advised to strengthen these factors through consistent policies, clear communication, and fair implementation to further improve employee performance and organizational competitiveness in the logistics industry.advised to strengthen both through fair and consistent policies to improve performance and competitiveness.